2004
DOI: 10.1073/pnas.0308594100
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive role of increased frequency of polypurine tracts in mRNA sequences of thermophilic prokaryotes

Abstract: The mechanism of an organism's adaptation to high temperatures has been investigated intensively in recent years. It was suggested that the macromolecules of thermophilic microorganisms (especially proteins) have structural features that enhance their thermostability. We compared mRNA sequences of 72 fully sequenced prokaryotic proteomes (14 thermophilic and 58 mesophilic species). Although the differences between the percentage of adenine plus guanine content of whole mRNAs of different prokaryotic species ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 51 publications
5
42
0
Order By: Relevance
“…The long standing hypothesis is that GC-richness of protein coding genes can not be considered as thermophilic signatures [17]. The above results confirm the findings of Paz et al [13] who reported abundance of polypurine tracts in thermophilic mRNA sequences, as purine loading of mRNAs is expected to reduce RNA-RNA interactions and thus prevent formation of double stranded RNA molecules [18]. Subsequently, frequency of each nucleotide for each of the three codon positions is analyzed.…”
Section: Nucleotide Compositional Bias As Ther-mophilic Adaptationsupporting
confidence: 77%
See 1 more Smart Citation
“…The long standing hypothesis is that GC-richness of protein coding genes can not be considered as thermophilic signatures [17]. The above results confirm the findings of Paz et al [13] who reported abundance of polypurine tracts in thermophilic mRNA sequences, as purine loading of mRNAs is expected to reduce RNA-RNA interactions and thus prevent formation of double stranded RNA molecules [18]. Subsequently, frequency of each nucleotide for each of the three codon positions is analyzed.…”
Section: Nucleotide Compositional Bias As Ther-mophilic Adaptationsupporting
confidence: 77%
“…Although considerable studies have focused on understanding the mechanisms that makes life possible under these conditions, it still remains unclear that whether it is due to external conditions or natural selection [4,7,[11][12][13][14]. In order to infer the molecular mechanistic adjustments to the thermal stress, it is desired to compare the genomic characteristics of hyperthermophiles with mesophilic genera.…”
Section: Introductionmentioning
confidence: 99%
“…Kawashima et al (2000) reported that in archaea a simple combination of purine (R) and pyrimidine (Y) dinucleotides, RR+YY-RY-YR, is linearly correlated with optimal growth temperature (OGT). An increased frequency of purine nucleotides in the coding strands contributes to thermostability (Paz et al, 2004). It has been reported that a simple summation of the purines adenine and guanine (A+G) is correlated with OGT (Lambros et al, 2003;Zeldovich et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As noted by other authors (e.g. Lao and Forsdyke 2000, Lambros et al 2003, and Paz et al 2004, the coding regions of many thermophilic genomes are purineloaded and possess codon biases that reflect that loading. Our method of using a "virtual coding strand" eliminated the variable of gene orientation.…”
Section: Cart With Genomic Signatures: An Accurate Discrimination Of mentioning
confidence: 96%